Visual archive South Eastern Europe : VASE - Österreichische Akademie der Wissenschaften; Karl-Franzens-Universität Graz (2025)
The main objective of the Visual Archive Southeastern Europe (VASE) is to assemble historical and contemporary visual materials from this region of Europe. VASE seeks to draw attention to the image as a primary source, to promote visual studies as a technique and method and thereby to enrich predominantly text-based historical-anthropological research. By providing access to different types of images – e.g. photographs and postcards – VASE aims to enhance reflection on (self-)images of Southeastern Europe, both within the academic community as well as in society in general.